2011
DOI: 10.2478/s13386-011-0022-9
|View full text |Cite
|
Sign up to set email alerts
|

Concordant 210Pb and 137Cs ages of black sea anoxic unconsolidated sediments

Abstract: Two independent geochronologic radiometric methods:137 Cs and 210 Pb were used to determine the sedimentation rate and subsequently to date the oldest sediments of a 50 cm core containing unconsolidated sediments collected at a depth of 600 m below sea surface in the anoxic zone of the Western Black Sea, off the Romanian town of Constanta. Both methods gave coincident value within experimental uncertainties of 0.42±0.20 mm·y -1 for 137 Cs and 0.49±0.03 mm·y -1 in the case of 210 Pb, within the Constant In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The Black Sea is an enclosed silled basin with an area of 422,000 km 2 and a maximum depth of 2212 m (Florea et al 2011). The water column is stratified, with the pycnocline and halocline both occurring at about 75 m depth in the centre of the basin and 200 m at the margins, and marking the boundary between oxygenated water above and euxinic, H2Ssaturated and saline deeper waters below (Arthur et al 1994, Florea et al 2011. At the seafloor, there is a topmost gelatinous flocculent surface layer about 2 cm thick overlying a further 2 cm of unlaminated grey/white carbonate-rich sediment (Pilskaln and Pike 2001).…”
Section: Black Seamentioning
confidence: 99%
See 1 more Smart Citation
“…The Black Sea is an enclosed silled basin with an area of 422,000 km 2 and a maximum depth of 2212 m (Florea et al 2011). The water column is stratified, with the pycnocline and halocline both occurring at about 75 m depth in the centre of the basin and 200 m at the margins, and marking the boundary between oxygenated water above and euxinic, H2Ssaturated and saline deeper waters below (Arthur et al 1994, Florea et al 2011. At the seafloor, there is a topmost gelatinous flocculent surface layer about 2 cm thick overlying a further 2 cm of unlaminated grey/white carbonate-rich sediment (Pilskaln and Pike 2001).…”
Section: Black Seamentioning
confidence: 99%
“…Black organicrich laminae with biogenic metal sulphides occur between the carbonate and terrigenous laminae(Pilskaln and Pike 2001, Schimmelmann et al 2016). The top flocculent layer is thought to be a permanent transition zone that hydraulically sorts particles by density(Pilskaln and Pike 2001).The varves have been independently dated using 210 Pb, 137 Cs and 14 C AMS, although the latter commonly gives older ages due either to the presence of "dead" carbon in Black Sea sediments or missing varves(Arthur et al 1994, Pilskaln and Pike 2001, Florea et al 2011.Although the highest countable varves beneath the flocculent layer date to about 1918 CE(Arthur et al 1994),Florea et al (2011) discerned the 1986 CE Chernobyl 137 Cs signal at between 5 and 10 mm depth (in samples collected in 2004 CE), which agrees with a 210 Pbdated accumulation rate of 0.49 ± 0.03 mm yr -1 . Groups of varves in Unit I have been correlated across the entire deeper basin…”
mentioning
confidence: 99%
“…Previous analysis of this core demonstrated that, by assuming a constant depositional rate, the maximum age of the sediments is about 1 ± 0.1 ky [18]. Given the quasi-regularity of lamina thickness (Figure 1), we have used the 210 Pb data for determination of an estimated age to different sections of the core.…”
Section: Discussionmentioning
confidence: 99%
“…Another peculiarity observed for the EF vertical profiles (Figure 3) is the significant fluctuation at depths varying between 15 to 25-30 cm, the same depths where the clay and carbonate contents reached the maximum variability (Figure 1b). By assuming for the entire column an age of about 1 ky [18], this sector could have an age between 300 and 600 y BP, which partially coincides with the Little Ice Age. Another possible explanation could be linked with the onset of the Industrial Revolution and its significant environmental impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation